Attitude dynamics of satellites with variable shape mechanisms using atmospheric drag torque and gravity gradient torque. (January 2023) - Miyamoto, Kiyona; Chujo, Toshihiro; Watanabe, Kei; Matunaga, Saburo
Abstract: Disturbance torques, such as atmospheric drag torque and gravity gradient torque, have always been an issue in attitude control for satellites in low Earth orbit. Although attitude control systems using disturbance torques has been studied with various methods, most previous research has focused on attitude control using aerodynamic stability to remove disturbances. We propose a new attitude control system that actively uses disturbance torque. This system controls the attitude using disturbance torques by changing the equilibrium point of the attitude motion by changing the shape of the satellite. We formulate the attitude dynamics of a variable-shape satellite as a preliminary study. This paper shows that the satellite attitude can be adjusted by varying the equilibrium point of attitude motion by changing the satellite shape. Also, we investigate the stability around the equilibrium point for each shape, and the results show the distribution of the stability index and the equilibrium point for each shape. Finally, we show that the attitude asymptotically converges to an equilibrium point by using the variable shape function and magnetic control. Highlights: A new attitude control system that uses variable-shape function and disturbance torques is proposed. Equilibrium point can be changed by changing shape of satellite. Attitude dynamics of variable-shape satellite is formulated. Relationship among the shapes, equilibrium points, and stability is investigated.